TINJAUAN HUKUM ISLAM TERHADAP BIAYA ADMINISTRASI PADA PEMBIAYAAN PENSIUNAN (Studi Kasus Di Bank Syariah Mandiri Kantor Cabang Pembantu Bogor Dramaga) - Adi Nugraha Wijaya; Tubagus Rifqy Thantawi; Azizah Mursyidah (SAHID BANKING JOURNAL, 2022)
This research is motivated by the existence of Bank Syariah Mandiri as one of the pioneers of the Islamic economy, as well as a means of accommodating the interests of the Indonesian people, especially Muslims whose goals can be realized by the Indonesian people. Bank Syariah Mandiri (BSM) has one product, namely the BSM Pension, where this product is a financing product specifically for retired State Civil Apparatuses. This research was conducted at the Sub-Branch Office of Bank Syariah Mandiri Bogor Dramaga which is located at Jl. Officer No. 151 Dramaga-Bogor (16680). This research took place from February to July 2020, the authors were interested in conducting this research because pension financing customers were burdened with administrative costs by the bank, the authors wanted to find out how the perspective of Islamic law was in taking these administrative costs. , To find out the problems in this study, the authors conducted qualitative research. The data collection method used in this research is by conducting interviews, observation and documentation. This data collection method is aimed at bank officers who usually directly serve retirees. Interviews, observations and documentation were carried out in person on March 18 2020 at the Bank Syariah Mandiri office, Dramaga Bogor Sub-branch Office. The analysis used in this research is descriptive qualitative. The results of the study show that taking administrative fees is permitted in accordance with the provisions of the DSN-MUI Fatwa Number 19/DSN-MUI/IV/2001 concerning Al-Qardh that the cost of the filing process is charged to the customer, provided that there must be certainty about what fees are used. During the application process, administration fees are taken at a reasonable rate so that they do not burden the customer, and do not make administrative costs a source of bank income.